Online GIS and spatial metadata - Green, David; Bossomaier, Terry (Taylor & Francis, 2002)
The WWW presents many new and exciting opportunities for GIS as well as numerous technical, practical and organisational challenges. This book covers the principles, standards and techniques for online GIS.